2019
DOI: 10.1038/s41467-019-13854-3
|View full text |Cite
|
Sign up to set email alerts
|

Descending motor circuitry required for NT-3 mediated locomotor recovery after spinal cord injury in mice

Abstract: Locomotor function, mediated by lumbar neural circuitry, is modulated by descending spinal pathways. Spinal cord injury (SCI) interrupts descending projections and denervates lumbar motor neurons (MNs). We previously reported that retrogradely transported neurotrophin-3 (NT-3) to lumbar MNs attenuated SCI-induced lumbar MN dendritic atrophy and enabled functional recovery after a rostral thoracic contusion. Here we functionally dissected the role of descending neural pathways in response to NT-3-mediated recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 66 publications
3
37
0
Order By: Relevance
“…NT‐3 has also been shown to enhance neuronal survival and stimulate regenerative sprouting following SCI (Han et al., 2019; Li et al., 2016; Tobias et al., 2003; Xu et al., 2020). Moreover, it can enhance the survival of OPCs, both in vitro and in vivo (Kumar et al., 1998).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NT‐3 has also been shown to enhance neuronal survival and stimulate regenerative sprouting following SCI (Han et al., 2019; Li et al., 2016; Tobias et al., 2003; Xu et al., 2020). Moreover, it can enhance the survival of OPCs, both in vitro and in vivo (Kumar et al., 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Another treatment strategy utilizes neurotrophic agents to promote neuronal survival and stimulate the regeneration of axons. Currently some of the most common neurotrophic agents utilized in spinal regeneration studies include brain‐derived neurotrophic factor (BDNF; Gransee et al., 2015; Hassannejad et al., 2019; Liu et al., 2017), glial cell line‐derived neurotrophic factor (GDNF; Chen et al., 2018; Haldeman & Manna, 2019; Tajdaran et al., 2016), and neurotrophic factor‐3 (NT‐3; Han et al., 2019; Li et al., 2016; Xu et al., 2020). In these studies, the application of neurotrophic factors can enhance neuron survival and axonal sprouting, depending on the neuronal population examined and the SCI model.…”
Section: Introductionmentioning
confidence: 99%
“…Contained within the spinal cord, PNs are well-suited to relay information to motor pools below a lesion site (Han et al, 2019 ). Many receive inputs from supraspinal motor systems, and after unilateral lesion, corticospinal tract (CST) or reticulospinal (ReST) tract axons can sprout onto cervical PNs to relay these motor commands past the lesion site (Bareyre et al, 2004 ; Filli et al, 2014 ).…”
Section: Plasticity Mechanisms That Are Hypothesized To Enable Ees Tomentioning
confidence: 99%
“…At the same time, anatomical studies have suggested that this proprioceptive input from below the level of the lesion interacts with extensive reorganization of the spinal proprioceptive circuitry (93)(94)(95)(96) that can allow the proprioceptive input to reach the cortex through interactions with reorganized supraspinal circuits (87,(97)(98)(99)(100). Therefore, the hindlimb proprioceptive information that is enabled through epidural stimulation replaces the hindlimb proprioceptive information we now know to exist in intact animals.…”
Section: Hindlimb Sensory Feedback To the Trunk Sensorimotor Cortex: mentioning
confidence: 99%